ANALISIS KINERJA SUMBER DAYA MANUSIA PADA USAHA AYAM BAKAR AA WAHYU CABANG CIRUAS DALAM MENDUKUNG KEMAJUAN USAHA - Indah Rahayu; Reva Tria Agustina; Fitri Khasanah; Ade Fauji (Nindikayla Institute, 2026)
This study aims to analyze the performance of human resources (HR) at the Aa Wahyu Grilled Chicken Business, Ciruas Branch, in supporting business progress. The study used a descriptive qualitative method with data collection techniques such as observation, interviews, and documentation. The results show that HR plays a crucial role in maintaining service quality, increasing work productivity, maintaining product quality, and enhancing customer satisfaction. Factors influencing HR performance include abilities and skills, work motivation, work discipline, work environment, leadership, compensation, training, and teamwork. Challenges faced include limited employee numbers, consistent performance during peak hours, and increasingly fierce business competition. This study concludes that good HR management is a key factor in supporting the development and sustainability of culinary businesses.